Both insulin and epidermal growth factor stimulate lipogenesis and acetyl-CoA carboxylase activity in isolated adipocytes. Importance of homogenization procedure in avoiding artefacts in acetyl-CoA carboxylase assay. - Haystead, T A (1986)
Epidermal growth factor (EGF) stimulates lipogenesis by 3-4-fold in isolated adipocytes, with a half-maximal effect at 10 nM-EGF. In the same batches of cells insulin stimulated lipogenesis by 15-fold. Freezing and prolonged homogenization of adipocytes results in release of large quantities of pyruvate carboxylase from broken mitochondria, and sufficient pyruvate can be carried through into assays for this enzyme to cause significant interference with assays of acetyl-CoA carboxylase in crude adipocyte extracts. This may account for the high amount of citrate-independent acetyl-CoA carboxylase activity reported to be present in adipocyte extracts in some previous publications. This problem may be eliminated by homogenizing very briefly without freezing. By using the modified homogenization procedure, EGF treatment of adipocytes was shown to produce an effect on acetyl-CoA carboxylase activity almost identical with that of insulin. Both messengers increase Vmax. without significant effect on the Ka for the allosteric activator, citrate.